Corporate reporting on solutions to wicked problems: Sustainable land management in the mining sector. Issue 48 (April 2015) - Barkemeyer, Ralf; Stringer, Lindsay C.; Hollins, James A.; Josephi, Ferdinand
Highlights: Mining stakeholders can play a key role in advancing land degradation neutrality. Mining company reports are analysed for sustainable and management (SLM) practices. This first analysis of its kind identifies a range of best SLM reporting practices. Corporate disclosures lack contextual detail, preventing insight into SLM practices. Interviews suggest the SLM discourse is poorly developed in the mining sector. Abstract: Land degradation is a wicked problem for social–ecological systems, addressed through international policy by the United Nations Convention to Combat Desertification (UNCCD). The UNCCD is striving towards land degradation neutrality – maintenance or improvement of the condition of the land – whereby degradation is prevented and reversed through sustainable land management (SLM) and restoration. Land degradation neutrality, and therefore SLM, is relevant to all land-based sectors. This paper focuses on the mining sector. It explores how mining companies and mining sector stakeholders conceptualize SLM; identifies the drivers of their engagement in SLM; examines how mining companies operationalize existing guidelines to report on SLM; and evaluates the implications of the ways in which companies report on SLM in terms of the UNCCD's efforts in moving towards land degradation neutrality. Our methodological approach includes semi-structured interviews with key mining and SLM stakeholders and content analysis of company sustainability reports. Findings identify a range of interpretations of SLM and suggest that companies are engaging in SLM largely due to the need to reduce their costs and risks. We find a variety of good and poor reporting practices. Differences in both SLM discourses and the quality of reporting have important implications in terms of stakeholders' abilities to understand and evaluate corporate SLM performance, their engagement in the implementation of the UNCCD, and ultimately, the progress made towards land degradation neutrality. Our findings suggest that the currently dominant format of corporate sustainability reporting does not lend itself easily to context-specific, wicked problems such as SLM. Furthermore, there is a need for improved communication, data sharing and knowledge management between mining and other SLM stakeholders; a need to seek further synergistic opportunities for reporting; and that the context of reporting needs to be more clearly presented if reports are to be more useful and meaningful in outlining SLM.